Macroscopic and Microscopic Studies on Sarcocystis Infection in Buffaloes - Public Health Alert - Sivajothi, S.; Reddy, B. Sudhakara (Animal Review, 2018)
Sarcocystosis is one of the important zoonotic parasitic diseases and commonly reported in buffaloes, cattle and pigs. Meat and meat products are the main sources of infection in human beings. The present study aimed to record the prevalence of Sarcocystosis in buffaloes during the time of slaughter. Out of 61 buffaloes slaughter for meat purpose, 38 showed the presence of macroscopic sarcocysts in different organs and they were in creamy colour lying parallel in between the muscle bundles. Distribution of the sarcocysts was noticed in the muscles of oesophagus, diaphragm, heart and base of the tongue. Microscopic examination of the stained impression smears collected from the mixed meat which is ready for sale from the 61 buffaloes, 52 were found positive for microscopic bradyzoites. In conclusion, Sarcocystis is more prevalent in buffaloes and diagnosis of the disease can be done by microscopic examination of the stained slide impression smears from the suspected meat along with the macroscopic examination of the muscles.